Hybrid Learning Approach Using Chamilo for Students of the Faculty of Tarbiyah dan Ilmu Keguruan, Institut Agama Islam Negeri (IAIN) Manado - Tubagus, Munir Bagus (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Learning Management System (LMS) is a learning process that utilizes information technology in the form of computers equipped with telecommunications facilities. The purpose of developing a Learning Management System is to facilitate and assist students in learning the subject of program evaluation. This research method is R & D (Research and Development), which is research to produce and test the effectiveness of these products. There are four stages in making e-learning, (1) Analysis of the system includes hardware, software, learning material, and student development, (2) Design includes instructional design analysis, teaching materials, and media (software) used, (3) Implementation, that is product and development of the resulting Learning Management System, (4) Evaluation, namely the Assessment stage by experts to test the feasibility of the system.“The sample of this study was 67 students from two classes who were enrolled in this study. The results showed that the average difference in pre-test and post-test scores was -8.83582. Whereas the test-t test Ho: pre-test = post-test gives the value t = -3.222 with degrees of freedom was 66. While the value p for two-sided tests 0.000 was smaller than α = 0.05. This data proves that the statistical hypothesis of Ho: pre-test = post-test is rejected, meaning that the average pre-test and post-test scores differ significantly. The findings of this research can be used to recommend implementing effective learning and teaching process using hybrid learning models, therefore improving students’ learning outcomes in higher education.